Pendidikan Islam Perspektif Manajemen - Eriyanto Eriyanto; Junaidi Junaidi (Jurnal Pendidikan Islam Indonesia, 2018)
Education in Islam should be managed as well as possible. Management of Islamic education is one way to improve the quality of people's lives from backwardness both morally, materially, and spiritually. In Islam, management is very important. This is seen by wise expression "something that is not organized is sometimes defeated by something that is vanity organized."